2021
DOI: 10.3390/brainsci11101282
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Inflammatory Cytokines and Antibodies Induce hnRNP A1 Dysfunction in Mouse Primary Cortical Neurons

Abstract: Multiple sclerosis (MS) is an inflammatory disease of the central nervous system with a significant neurodegenerative component. Dysfunctional RNA-binding proteins (RBPs) are causally linked to neuronal damage and are a feature of MS, including the mislocalization of the RBP heterogeneous nuclear ribonucleoprotein A1 (A1). Here, we show that primary neurons exposed to pro-inflammatory cytokines and anti-A1 antibodies, both characteristic of an MS autoimmune response, displayed increased A1 mislocalization, str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 53 publications
(73 reference statements)
0
9
1
Order By: Relevance
“…Collectively, our data highlight an important role for hnRNP A1 in proper OL functioning and survival and suggest a potential mechanism of OL damage and death in MS that involves hnRNP A1 dysfunction. This adds to our ongoing work (Anees et al, 2021; Li et al, 2021; Libner et al, 2020; Salapa et al, 2018; Salapa, Hutchinson, et al, 2020; Salapa, Libner, & Levin, 2020) that hnRNP A1 dysfunction in neurons contributes to neurodegeneration in MS and its models. Along with the data presented here, in which we show that hnRNP A1 dysfunction in OLs leads to OL death, damage and subsequent demyelination, suggest that together, hnRNP A1 dysfunction in both OLs and neurons combine to contribute to central nervous system damage and subsequent disability in MS. Future studies should expand on the role hnRNP A1 dysfunction may play in the ability of OLs to properly maintain or produce new myelin.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Collectively, our data highlight an important role for hnRNP A1 in proper OL functioning and survival and suggest a potential mechanism of OL damage and death in MS that involves hnRNP A1 dysfunction. This adds to our ongoing work (Anees et al, 2021; Li et al, 2021; Libner et al, 2020; Salapa et al, 2018; Salapa, Hutchinson, et al, 2020; Salapa, Libner, & Levin, 2020) that hnRNP A1 dysfunction in neurons contributes to neurodegeneration in MS and its models. Along with the data presented here, in which we show that hnRNP A1 dysfunction in OLs leads to OL death, damage and subsequent demyelination, suggest that together, hnRNP A1 dysfunction in both OLs and neurons combine to contribute to central nervous system damage and subsequent disability in MS. Future studies should expand on the role hnRNP A1 dysfunction may play in the ability of OLs to properly maintain or produce new myelin.…”
Section: Discussionmentioning
confidence: 70%
“…Collectively, our data highlight an important role for hnRNP A1 in proper OL functioning and survival and suggest a potential mechanism of OL damage and death in MS that involves hnRNP A1 dysfunction. This adds to our ongoing work (Anees et al, 2021;Li et al, 2021;Libner et al, 2020;Salapa et al, 2018;Salapa, Hutchinson, et al, 2020;) that hnRNP A1 dysfunction in neurons contributes to neurodegeneration in MS and its models.…”
Section: Hnrnp A1 Dysfunction Disrupts Ol Morphology Viability and Ac...mentioning
confidence: 62%
See 2 more Smart Citations
“…In fact, it is well-known that RBPs are key players in the RNA metabolism especially in neurons where they are particularly expressed [ 96 ]. Recently, it has been demonstrated that pro-inflammatory mediators, such as IFN-γ and TNF-α, are able to trigger hnRNP A1 mislocalization and stress granule formation in murine primary neuron culture, with consequently neurite damage [ 97 ]. Specifically, SAFA (also known as hnRNP U) was found to be involve in protecting cells from viral infections, since it acts at a nuclear sensor for viral dsRNA and is able to trigger the activation of super-enhancer of anti-viral gene expression, such as IFNB1 [ 98 ].…”
Section: The Role Of Neuroinflammation In Viral Infection and Neurode...mentioning
confidence: 99%